1994
DOI: 10.2134/jpa1994.0441
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Soil Test Phosphorus and Potassium for Variable-Rate Fertilizer Application

Abstract: Variable‐rate fertilizer (VRF) application requires knowledge of the spatial variability of soil test P and K within a field. The objectives of the study were to: (i) evaluate cell (area) vs. point soil sampling, both on a grid basis, and (ii) compare methods for mapping location specific soil test data. Soils in two central Wisconsin fields were sampled with two methods; study site soils included two alfisols and one entisol. The grid‐cell method involved dividing fields into 318‐ft square cells and compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
103
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(110 citation statements)
references
References 4 publications
0
103
0
7
Order By: Relevance
“…Some of them found that kriging method outperformed IDW or splines because of a careful choice of the optimal number of neighboring points, variogram model and the variogram parameters (Laslett et al, 1987;Leenaers et al, 1990;Hosseini et al, 1994;Kravchenko and Bullock, 1999;Panagopoulos et al, 2006); however, the others showed that kriging was not better than the other two methods (Weber and Englund, 1992;Wollenhaupt et al, 1994;Gotway et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them found that kriging method outperformed IDW or splines because of a careful choice of the optimal number of neighboring points, variogram model and the variogram parameters (Laslett et al, 1987;Leenaers et al, 1990;Hosseini et al, 1994;Kravchenko and Bullock, 1999;Panagopoulos et al, 2006); however, the others showed that kriging was not better than the other two methods (Weber and Englund, 1992;Wollenhaupt et al, 1994;Gotway et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Em alguns estudos se constatou maior acurácia da interpolação por IPD que a krigagem (Musa et al, 2002), enquanto em outros se verificou melhor desempenho da krigagem (Kravchenko & Bullock, 1999;Zimmerman et al, 1999) ou estimativas muito próximas entre os dois métodos, apesar da superioridade da krigagem (Conde & Yamamoto, 1996;Kravchenko, 2003). Wollenhaupt et al (1994) compararam o IPD com a krigagem no mapeamento de níveis de P e K em solos e verificaram maior acurá-cia do método IPD; entretanto, Kravchenko & Bullock (1999), estudando a interpolação por krigagem ordinária e IPD no mapeamento de propriedades de solo constataram, na maioria das situações, melhor desempenho da krigagem. Kravchenko (2003) também verificou melhor desempenho da krigagem com relação ao IPD no mapeamento de propriedades de solo; porém, quando não foi possível obter parâme-tros confiáveis nos semivariogramas, a krigagem apresentou menor acurácia.…”
Section: Introductionunclassified
“…Gotway et al (1996) found that the IDW method generated more accurate results for mapping soil organic matter and soil NO 3 levels. Wollenhaupt et al (1994) compared these two interpolation techniques and concluded that IDW was more accurate for mapping P and K levels soil. Mueller et al (2004) observed that for the optimal parameters of the method, the accuracy of IDW interpolation generally equaled or exceeded the accuracy of Kriging at each scale of measurement.…”
Section: Introductionmentioning
confidence: 99%